Adsorption and Sensing Performances of Pristine and Au-Decorated Gallium Nitride Monolayer to Noxious Gas Molecules: A DFT Investigation - Li, Zhihui; Jia, Lufen; Chen, Jianxing; Cui, Xiaosen; Zhou, Qu (Frontiers in Chemistry, 2022)
In this paper, the adsorption of noxious gas molecules (NO, Cl2 and O3) on the GaN and Au decorated GaN was systematically scrutinized and the adsorption energy, bond length, charge, density of state (DOS), partial density of state (PDOS), electron deformation density (EDD) and orbitals were analyzed by the density functional theory (DFT) method. It is found that the interaction between NO and pristine GaN is physical adsorption, while the GaN chemically reacts with Cl2 and O3. These observations suggest that the pristine GaN may be a candidate for the detection of the Cl2 and O3. The highly activated Au decorated GaN can enhance the adsorption performance toward NO and convert the physical adsorption for NO into chemical adsorption, explaining the fact that precious metal doping is essential for regulating the electronic properties of the substrate material. This further confirms the well-established role of Au decorated GaN in NO gas-sensing applications. In addition, the adsorption performance of Au decorated GaN for Cl2 and O3 molecules is highly improved, which provides guidance to scavenge toxic gases Cl2 and O3 by Au decorated GaN material.